2011
DOI: 10.1093/hmg/ddr192
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 7p11.2 (EGFR) variation influences glioma risk

Abstract: While gliomas are the most common primary brain tumors, their etiology is largely unknown. To identify novel risk loci for glioma, we conducted genome-wide association (GWA) analysis of two case-control series from France and Germany (2269 cases and 2500 controls). Pooling these data with previously reported UK and US GWA studies provided data on 4147 glioma cases and 7435 controls genotyped for 424 460 common tagging single-nucleotide polymorphisms. Using these data, we demonstrate two statistically independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 26 publications
5
157
1
2
Order By: Relevance
“…In the present study, we investigated four variants annotating the 7p11.2 (EGFR) region that have previously been identified as associated with glioma risk; two variants were identified through a GWAS (rs2252586 and rs11979158; ref. 13), and two variants were identified through a candidate gene approach (rs4947979 and rs4947986; ref. 19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated four variants annotating the 7p11.2 (EGFR) region that have previously been identified as associated with glioma risk; two variants were identified through a GWAS (rs2252586 and rs11979158; ref. 13), and two variants were identified through a candidate gene approach (rs4947979 and rs4947986; ref. 19).…”
Section: Discussionmentioning
confidence: 99%
“…The two variants at 9p21.3 (rs4977756 and rs1412829) were found independently, but are in linkage disequilibrium (D 0 ¼ 0.76), whereas the two variants at 7p11.2 (rs11979158 and rs2252586) were found through the same study, but are less frequently co-inherited (D 0 ¼ 0.56). Variants in 20q13.3 (RTEL1), 5p15.33 (TERT), and 9p21.3 (CDKN2B-AS1) are largely shown to be primarily associated with higher grade tumors (11,13,15,16), though Jenkins and colleagues found rs2736100 (TERT) to display a similar association with all glioma subtypes (16) and Simon and colleagues found rs4977756 (CDKN2B) to not be correlated with tumor grade (15). Conversely, variants in 11q23.3 (PHLDB1) and 8q24.21 (CCDC26) are primarily associated with lower grade tumors and oligodendroglioma (11,13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous glioma GWAS have identified seven risk loci, including two genes (TERT and RTEL1) involved in telomere dynamics [6][7][8][9][10]. Somatically acquired mutations in the TERT promoter increase TERT expression and are Dianhong Wang, Enxi Hu, and Pei Wu have contribute equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are extremely rare, however, and much of the excess familial risk is likely to be a consequence of multiple lowrisk variants. Indeed, genome-wide association studies (GWASs) [3][4][5][6] have identified seven independent risk loci for glioma at 5p15.33 (TERT ), 7p11.2 (EGFR; two independent loci), 8q24.21 (CCDC26 ), 9p21.3 (CDK N2 A / CDK N2B / CDK N2B AS ), 20q13.33 (RTEL1) and 11q23.3 (PHLDB1). Given that the arrays used in these GWASs were based on data from early haplotype maps and included only relatively common variants, all of the risk variants identified in these studies were of the common/lowpenetrance type.…”
Section: Editorialmentioning
confidence: 99%